1988
DOI: 10.1038/331622a0
|View full text |Cite
|
Sign up to set email alerts
|

An H+-ATPase in opposite plasma membrane domains in kidney epithelial cell subpopulations

Abstract: Vectorial solute transport by epithelia requires the polarized insertion of transport proteins into apical or basolateral plasmalemmal domains. In the specialized intercalated cells of the kidney collecting duct, the selective placement of an apical plasma membrane proton-pumping ATPase (H+-ATPase) and of a basolateral membrane anion-exchange protein results in transepithelial proton secretion. It is currently believed that amino-acid sequences of membrane proteins contain critical signalling regions involved … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
170
2

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 268 publications
(177 citation statements)
references
References 18 publications
5
170
2
Order By: Relevance
“…On the basis of their ultrastructure and the presence of H + -ATPase and carbonic anhydrase, the lamprey IMRC is a type of epithelial cell that also occurs, for example, in the amphibian epidermis, the toad and turtle urinary bladders and renal collecting duct [7,11,13,30,31]. This cell type comprises three subtypes: one (A) containing the H + -ATPase in its apical membrane and an HCO 3 − /Cl − exchanger in its basolateral membrane, another (B) exhibiting the opposite locations of the H + pump and the anion exchanger and a third (C) in which the H + pump and the anion exchanger are both located in the apical membrane [32][33][34]. Whereas the subtypes A and B are involved in acid-base regulation, secreting H + or HCO 3 − , respectively, the subtype C has been held responsible for the uptake of Cl − [32][33][34].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the basis of their ultrastructure and the presence of H + -ATPase and carbonic anhydrase, the lamprey IMRC is a type of epithelial cell that also occurs, for example, in the amphibian epidermis, the toad and turtle urinary bladders and renal collecting duct [7,11,13,30,31]. This cell type comprises three subtypes: one (A) containing the H + -ATPase in its apical membrane and an HCO 3 − /Cl − exchanger in its basolateral membrane, another (B) exhibiting the opposite locations of the H + pump and the anion exchanger and a third (C) in which the H + pump and the anion exchanger are both located in the apical membrane [32][33][34]. Whereas the subtypes A and B are involved in acid-base regulation, secreting H + or HCO 3 − , respectively, the subtype C has been held responsible for the uptake of Cl − [32][33][34].…”
Section: Resultsmentioning
confidence: 99%
“…This cell type comprises three subtypes: one (A) containing the H + -ATPase in its apical membrane and an HCO 3 − /Cl − exchanger in its basolateral membrane, another (B) exhibiting the opposite locations of the H + pump and the anion exchanger and a third (C) in which the H + pump and the anion exchanger are both located in the apical membrane [32][33][34]. Whereas the subtypes A and B are involved in acid-base regulation, secreting H + or HCO 3 − , respectively, the subtype C has been held responsible for the uptake of Cl − [32][33][34]. In the epithelium of the turtle bladder, the apical surface area of subtype A cells becomes enlarged under acidotic conditions through exocytosis of cytoplasmic membranous tubules and vesicles containing the H + -ATPase [19,35].…”
Section: Resultsmentioning
confidence: 99%
“…Immunoreactivity for cytokeratin was found in principal cells of the collecting duct, but not in other regions, including the connecting segment. The specific labeling of collecting ducts in keratin immunohistochemistry of the kidney may be explained by the narrow reactivity of the cytokeratin antibodies used, which were raised against epidermal keratins (SUN et al,1979;SCHLEGEL et al, 1980 (BROWN et al, 1988). Antibodies raised against band 3, one of the Cl-/HCO3-exchangers, can selectively detect type A cells (VERLANDER et al, 1988).…”
Section: Discussion Os-3-immunoreacitve Cells Are Type B Intercalatedmentioning
confidence: 99%
“…These studies, now more than 20 yr old, suggest that the reversal of direction of transepithelial H ϩ transport is due to conversion of the HCO 3 -secreting cell type to an acid-secreting cell. In both cell types, Brown et al 8 found that it is the same vacuolar ATPase that is located in the apical membrane of the ␣ form or in the basolateral membrane of the ␤ cell type. The reversal of polarized distribution of the H ϩ -ATPase attracted much attention among cell biologists, since it contradicted the deterministic idea (current in the mid-1980s) that polarized SPECIAL ARTICLE www.jasn.org sorting of proteins in epithelia was due to the presence of targeting sequences in the proteins and hence was "immutable.…”
Section: Urinary Acidification In the Cortical Collecting Tubulementioning
confidence: 99%